Integrasi Nilai Islam dan Budaya Lokal Madura dalam Pembentukan Harmoni Sosial-Ekonomi di Pondok Pesantren Nazhatut Thullab Sampang - Qadarin, Maryam; Islamiyah, Hidayatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Islamic boarding schools (pesantren) serve as vital institutions for both religious education and socio-economic empowerment. This study investigates the integration of Islamic values and Madurese local culture in fostering socio-economic harmony at Pondok Pesantren Nazhatut Thullab Sampang. Adopting a mixed-methods approach, quantitative data from 60 respondents were analyzed using SEM-PLS, complemented by qualitative insights from seven key informants. Findings reveal that Islamic values—particularly honesty (shiddiq) and trustworthiness (amanah)—significantly contribute to socio-economic harmony (β = 0.435), while local cultural values such as hard work (karkar colpe) and religiosity (abantal sadhat, apajung Alla, asapo’ salawat) exert a slightly stronger influence (β = 0.521). The synergy of both value systems cultivates ethical, just, and barakah-oriented economic practices. Through the One Pesantren One Product (OPOP) initiative, the pesantren successfully harmonizes spiritual and material dimensions, illustrating how faith-based institutions can promote sustainable socio-economic development grounded in local wisdom.